Protection of the Rights of Parties, Participants and Third Parties During Enforcement in Republic of North Macedonia - Etemi-Ademi Bukurije; Zendeli Emine (SEEU Review, 2021)
The aim of this paper is to analyze the protection offered to parties, participants and third parties during enforcement, as one of the most important requirements of the enforcement procedure. Having in mind that bailiffs except for implementing enforcement, they are also competent to determine the means by which creditors’ claims will be fulfilled. The realization of the creditors’ claims does not mean use of any kind of measure or enforcement procedural activity. In this context the authors review ways in which debtors and their family members can be protected during enforcement actions, such as measures of exclusion and restriction of enforcement on the debtor’s items and income. Furthermore, the authors elaborate other legal and important ways for protection of parties, participants and third parties, such as opposition to illegality and complaints provided by the Law on Enforcement.